Local Negotiation of Change: Historiography of Modern Turkey and the Study of Provincial Anatolian Towns - Alexandros Lamprou (Siyasal: Journal of Political Sciences)
The article reviews the scholarly bibliography on provincial Turkish towns during the Early Republican Period with a specific emphasis on the study of the negotiation of social change at the provincial level. The article discusses the strengths and limitations of a body of work published since the 1960s and evaluates their position and contribution in the historiography of modern Turkey. Up to the late 1990s and the opening of the State Archives of the Republican Period, a tendency occurred to overlook the study of provincial towns in favor of major cities and villages. Post-2000 historiography that addresses sociopolitical change increasingly produces works that consider provincial towns; nevertheless, space is mostly regarded as a necessary spatial container of the process under study and, as such, rarely receives critical engagement. The article considers the dominant periodization of the literature, which truncates the history of modern Turkey before and after 1923, as extremely limiting in scope. Thus, it suggests that the narrowing of the spatial– geographical perspective (going local) and the widening of the time frame beyond the 1923–1950 period are promising directions for the research on sociopolitical changes during the late Ottoman Empire and republican Turkey.